Relapse of clinical symptoms of COVID-19 or probable reinfection in a laboratory professional: a case report from Northeast Brazil (Research, Society and Development, 2021)
Healthcare professionals constitute one of the groups that are most vulnerable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Herein, we report the case of a non-overweight and non-smoking 42-year-old woman with thrombophilia due to methylenetetrahydrofolate reductase (MTHFR) gene mutation, hereditary renal cysts, and no history of diabetes or arterial hypertension, who presented the first symptoms between 10 and 17 August 2020, with a SARS-CoV-2-positive naso-oropharyngeal swab by qualitative real-time polymerase chain reaction (RT-PCR). However, the result for SARS-CoV-2 immunoglobulin G (IgG) was non-reactive 41 days after (21 September 2020) the onset of symptoms. Nevertheless, on 7 October 2020 (57 days after the first symptoms), the patient presented new symptoms suggestive of COVID-19, with another SARS-CoV-2-positive RT-PCR result, and on 21 October 2020, SARS-CoV-2 immunoglobulin G was positive. Considering this, we interrogated the results to determine whether the case was reinfection or reactivation. This outcome highlights the importance of surveillance over relapses or reinfections.